1993
DOI: 10.1007/bf01982941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ovulation by a triphasic gestodene-containing oral contraceptive

Abstract: The minimal effective dose of gestodene for inhibition of ovulation was studied in 30 female volunteers. Daily doses of 10 micrograms to 50 micrograms gestodene were given orally for 21 days. A control cycle prior to treatment and a treatment cycle were monitored for LH, FSH, estradiol, progesterone and cervical score. At a daily dose of 40 micrograms of gestodene, 6/7 volunteers exhibited inhibition of ovulation and 1/7 had a cycle with luteal insufficiency. Ovulation was inhibited in all volunteers on 50 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…17,[40][41][42]51,54 Phasic COCs Table 3 shows the studies performed with triphasic (Tri) or biphasic (Bi) COCs. 8,17,18,23,28,32,33,42,43,49,[56][57][58][59][60][61][62][63] Overall, 21 out of 460 (4.6%) subjects were found to have ovulated. Differences between the various types of COC were observed, with the ovulation incidence ranging from 0.0% to 8.0%.…”
Section: 0mentioning
confidence: 99%
See 2 more Smart Citations
“…17,[40][41][42]51,54 Phasic COCs Table 3 shows the studies performed with triphasic (Tri) or biphasic (Bi) COCs. 8,17,18,23,28,32,33,42,43,49,[56][57][58][59][60][61][62][63] Overall, 21 out of 460 (4.6%) subjects were found to have ovulated. Differences between the various types of COC were observed, with the ovulation incidence ranging from 0.0% to 8.0%.…”
Section: 0mentioning
confidence: 99%
“…Another study assessed the effect of missing two doses of TriLNG/EE and reported one ovulation in 10 women; 32 progesterone was measured every 2 days. The third study unfortunately only measured progesterone on Days 4,8,10,12,18 or 19 and therefore levels during the critical days for escape ovulation were not taken into account. 62 Of the 46 women studied, four (8.7%) ovulated.…”
Section: 0mentioning
confidence: 99%
See 1 more Smart Citation